From Industry X to Industry 6.0: Antifragile Manufacturing for People, Planet, and Profit with Passion - Kuosmanen Pauli; Villman Tero; Annanperä Elina; Jurmu Marko; Kaivo-oja Jari; Kettunen Petri; Knudsen Mikkel; Lauraéus Theresa; Majava Jukka; Porras Jari (Allied ICT Finland (AIF), 2022)
This white paper addresses the potential pathways the Finnish industry must take in order to be the strategic leader and driver towards defining “Industry 6.0”. The recent global economic situation has revealed that the Finnish industry is affected by risks caused by the pandemic, global supply chains and dependency of suppliers all around the world. Therefore, we need to build up a completely new industrial revolution, in which antifragility is the design principle to increase our resilience to future stressors and global shocks. Like earlier industrial revolutions, advances in technology have paved the way to creating growth and well-being. Disruptive technologies, such as 3D printing and AI are an opportunity in localization of manufacturing back to Finland. The global climate crisis requires us to be at the forefront of a strategy that creates an impact on the environment, economy, and society. Here, the Finnish ICT expertise can solve problems, as long as the support of taking research results out into the industry is supported. The essential component in creating intelligent solutions and new business is data. Long-term development programs are needed for understanding what the use of data unlike ever before will imply for businesses, customers, ethics and regulations.
Industry 6.0 is defined in this paper as “Ubiquitous, customer-driven, virtualized, antifragile manufacturing”. It is characterized on one hand by customer-centric, highly customized lot-size-1 thinking, on the other hand by hyperconnected factories, with dynamic supply chains, where data flows across domains. These also change the role of humans as productions workers, as they become part of the interconnected environment and need to handle the digital, optimized production. While we already have strengths that prepare us to lead the next industrial revolution, we also have serious shortcomings. We need to raise the level of ICT knowledge across the industry; we need multidisciplinary research, development and innovation, and a strategy for long-term public commitment and significant investments.
We propose that Finland assumes a strong vision: Industry 6.0 is defined in Finland by proactive game-changing actions. This vision is realized in a long-term commitment to implementing an agenda of the following. 1) Finland nominates a Science and Technology minister to steer the activities. Their task would be to steer the implementation of the agenda holistically. 2) Current smart-specialization strategies need to be specified more carefully in order to utilize funding from the European Regional Development Fund (ERDF) more efficiently and in a coordinated matter. 3) Creation of the Virtual Industry 6.0 University, and approximately 10 new Industrial ICT professors and additional postdocs are needed to fill the gaps. 4) Creation of a test factory opening access of the environments broadly and serving as a testbed for Finnish winning platforms. With the network-based test factory, we can create a new pilot model in Finland combining the models of smart specialization, smart co-creation and shared RDI environments to ensure our industrial competitiveness. 5) Establishing a digital transformation accelerator for Finnish industry, aligning the accelerator to European Digital Innovation Hubs selections.